Developing Mathematics Learning Model of Thinking Empowerment by Question (TEQ) with TAI Setting to Improve Students’ Metacognition Ability (International Journal of Active Learning, 2018)
The method used in the development of mathematics learning model of Thinking Empowerment by Question (TEQ) with TAI setting is R D through 4-D steps, i.e., define, design, develop and disseminate. The subjects in the implementation of the model are the seventh-grade students of one of the junior high schools in Yogyakarta in the academic year 2017/2018 on the plane material. The method used in the model implementation is the quasi-experimental one group pretest-posttest design. Metacognition ability obtained used closed questionnaire. This model is based on the value of count proven to improve students' metacognition ability.